Women's Lived Experiences of Cohabitation: A Phenomenological Study - bahareh kakavand; anahita khodabakhshi-koolaee (Kerman University of Medical Sciences, 2021)
Introduction: The phenomenon of cohabitation or what is known in Iran as "white marriage" has presented women with new psychological and social challenges. The present study aimed to address the lived experience of cohabiting women. Methods: This qualitative and descriptive study was conducted using a phenomenological approach. The participants were 17 women who were selected through purposive sampling from among those who referred to health centers in District 22 of Tehran in 2018. The data were collected using semi-structured interviews with the participants and were saturated after 17 interviews. The collected data were analyzed using Colaizzi's seven-step method. Results: The women's psychological and emotional needs were classified into three main themes including "experiencing a relationship with a partner with fear and hope", "satisfaction of emotional, psychological, and sexual needs" and "concerns about an uncertain future". Conclusion: The main motivation for the women to be involved in this relationship was their disinterest in accepting responsibility. They also considered this relationship as a way to satisfy their sexual needs. Following these results, family and marriage counselors should take into account the serious harm that such relationships will have on the lives of future women.